2010
DOI: 10.1177/1363461510382154
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acculturation in Suicidal Ideation among Second-Generation Immigrant Adolescents in France

Abstract: This study explored the contributions of sociocultural and psychopathological factors to suicidal ideation among adolescents. A sample of 292 French high school students with an immigrant background completed a questionnaire assessing suicidal ideation, borderline personality traits, depressive symptoms, parental attachment, life events, acculturation orientations, ethnic identity, cannabis and alcohol consumption, socioeconomic status and academic failure. Although stressful life events, depressive symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 61 publications
0
20
0
6
Order By: Relevance
“… Pattern of victimization in schools, in part based on immigrant generation Spencer and Le [ 29 ] Cross Sectional USA Total n = 329 Cambodian = 120 of 15 years Chinese = 64 of 14 years Lao/Mien = 67 of 15 years Vietnamese = 86 of 14 years In all samples, the ratio of males and females fairly equally distributed Peer delinquency, parental engagement, serious violence and family/partner violence Van Bergen et al [ 39 ] Longitudinal Netherlands Total n = 4,527 of young females Dutch = 3,090; Moroccan = 557; Turkish = 614; Suriname = 266 Age = 14–16 years The prevalence of non-fatal suicidal behaviour of the sampled population and examines risk factors in non-western female immigrant adolescents compared to majority female adolescents Van Bergen et al [ 65 ] Longitudinal Netherlands Total n = 249 Turkish adolescents Age = 12–18 years Female sample 53 %; Male 47 % The prevalence of suicidal ideation and the vulnerability across several ethnic minorities versus ethnic majority adolescents Also examine whether ethnic minority adolescents are at risk for suicidal ideation because of a family background of migrants, social-economic position and certain family factors – influence psychological constellations. Van Leeuwen [ 56 ] Cross sectional France Total n = 292 students French high school girls = 122; French high school boys = 170 Age = 15–21 years Role of acculturation in suicidal ideation among second generation immigrant adolescents in France Ying and Han [ 42 ] Longitudinal USA Total n (wave 1) = 5,262 adolescents Total n (wave 2) = 4,288 adolescents Vietnamese 48.4 % Laotian 26.3 % Cambodian 16.5 % Hmong 8.8 % Males 50.4 % and Females 49.6 % Intergenerational conflict and depressive symptomatology …”
Section: Resultsmentioning
confidence: 99%
“… Pattern of victimization in schools, in part based on immigrant generation Spencer and Le [ 29 ] Cross Sectional USA Total n = 329 Cambodian = 120 of 15 years Chinese = 64 of 14 years Lao/Mien = 67 of 15 years Vietnamese = 86 of 14 years In all samples, the ratio of males and females fairly equally distributed Peer delinquency, parental engagement, serious violence and family/partner violence Van Bergen et al [ 39 ] Longitudinal Netherlands Total n = 4,527 of young females Dutch = 3,090; Moroccan = 557; Turkish = 614; Suriname = 266 Age = 14–16 years The prevalence of non-fatal suicidal behaviour of the sampled population and examines risk factors in non-western female immigrant adolescents compared to majority female adolescents Van Bergen et al [ 65 ] Longitudinal Netherlands Total n = 249 Turkish adolescents Age = 12–18 years Female sample 53 %; Male 47 % The prevalence of suicidal ideation and the vulnerability across several ethnic minorities versus ethnic majority adolescents Also examine whether ethnic minority adolescents are at risk for suicidal ideation because of a family background of migrants, social-economic position and certain family factors – influence psychological constellations. Van Leeuwen [ 56 ] Cross sectional France Total n = 292 students French high school girls = 122; French high school boys = 170 Age = 15–21 years Role of acculturation in suicidal ideation among second generation immigrant adolescents in France Ying and Han [ 42 ] Longitudinal USA Total n (wave 1) = 5,262 adolescents Total n (wave 2) = 4,288 adolescents Vietnamese 48.4 % Laotian 26.3 % Cambodian 16.5 % Hmong 8.8 % Males 50.4 % and Females 49.6 % Intergenerational conflict and depressive symptomatology …”
Section: Resultsmentioning
confidence: 99%
“…These children are often referred to as "second generation immigrants" (15,16). Second generation immigrants, according to Berry's acculturation theory, can be at risk of psychological distress due to conflicting cultures between their parents' country of birth and their own country of birth (17,18). Moreover, second generation immigrants may experience socio-economic difficulties or disadvantages, which could increase their risk of developing mental disorders.…”
Section: Patterns Of Global Migrationmentioning
confidence: 99%
“…Evidence from individual-level investigations research confirms these grouplevel effects. For example, Leeuwen et al (41) found individualistic values to be risk factor for suicidal ideation among immigrant adolescents in France. In a study of Australian university students Scott et al (42) found students with strong individualistic values (idiocentrism) to be less satisfied with, and less inclined to seek social support, and presenting higher levels of hopelessness and suicide ideation.…”
mentioning
confidence: 99%